Ichneumonid wasps of the subfamily Mesochorinae: new replacement names, combinations and an updated key to the World genera (Hymenoptera: Ichneumonidae) - Araujo, Rodrigo O.; Vivallo, Felipe; Santos, Bernardo F. (Zootaxa, 2018)
Mesochorinae is a relatively small but widely distributed subfamily of Ichneumonidae, with most species occurring in the Neotropical Region. Currently, there are two classifications in use regarding mesochorine genera, causing numerous taxonomic conflicts. To resolve nomenclature conflicts, seven new replacement names and twelve new combinations are proposed for species now recognized as members of Mesochorus Gravenhorst. Herein the synonymy of Plectochorus Uchida and Stictopisthus Thomson  with the genus Mesochorus s. lat. is reaffirmed, supported by the following shared character states: transverse subantennal carina partially or completely developed; supraclypeal area evenly convex, without median protrusion; clypeus not separated from supraclypeal area by depression or groove; and hind wing without vein Cu1b. An updated key to the World genera of Mesochorinae is also presented.